DEGENERATIVE SCOLIOSIS: A CASE REPORT - I Ketut Martiana; M Mukaddam Alaydrus (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: Scoliosis in adults is a spinal deformity in adult patients with a Cobb angle of more than 10° in the coronal plane. Degenerative scoliosis is a term used for the presence of spinal coronal deviation in the elderly population due to segment degeneration. This case report presents a quite different management option, namely applying intraoperative vertebral correction to the subject. The operative procedure carried out on the patient has experienced success as indicated by improvement in symptoms and curve progressiveness in patients.Case: A patient suffers degenerative scoliosis at Surabaya RKZ Hospital. Data is taken from medical records, patient clinical records, home visits, and physical examination of patients.Discussion: From the results of the post op clinical examination, it was found that pain complaints improved compared to pre-op complaints. From the results of the post op radiological examination, the position of fixation was good, there was no spondylolisthesis, lumbar dextroscoliosis (+), lumbar spondylosis (+), drain tip as high as Th12-L1.Conclusion: Giving operative management can directly improve the patient's quality of life and reduce symptoms experienced in a shorter time.